PERANCANGAN MEDIA PENYEBARAN INFORMASI SERTA SEBAGAI MEDIA PENDAFTARAN SISWA BERBASIS WEB - wulan nurhasanah; Ahmad Anas (Jurnal Komputer dan Teknologi, 2025)
School information systems and New Student Admisssion (PPDB) are an important part of managing educational institutions. At PAUD Tunas Karya, the information system and PPDB are considered less effective because they still use brochures and manual registration, which causes long queues and slow data management. Based on this problem, the author designed a website-based school profile and PPDB information system using the HTML and MYSQL as a database. The results of research at PAUD Tunas Karya can be concluded that by designing a website-based school profile and PPDB information system, it can help increase the dissemination of information and facilitate the PPDB process so that it is more efficient.